Victimization and fear of crime in an entertainment district crime “hot spot:” A test of structural-choice theory - Cochran, John K. (American journal of criminal justice, 2000)
Theories of criminal opportunity and criminal victimization (lifestyles, routine activities, and structuralchoice) all stress the convergence of motivated offenders, suitable targets, and the absence of guardianship in time and space. They each assert the chances of victimization increase as proximity to motivated offenders, exposure to highrisk environments, target attractiveness, and ineffective guardianship increase. This study tests Miethe and Meier’s structuralchoice theory by examining domainspecific victimization and fear of crime among patrons of an entertainment district crime “hot spot. ”Regression results show both victimization experience and fear of crime are associated significantly with indicators of proximity and guardianship, but not with exposure or target attractiveness. White patrons of this area are more likely to be victimized, nonwhites report significantly higher levels of fear.